Is There Effect of Murottal Therapy? Pregnancy Response with Spiritual Islamic Nursing Care Application - Nur Hidayah; Kristan Kristan; Ika Kartina; Muslimin Ardi (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2021)
The Spiritual Islamic Nursing Care (SINC) application is an innovation in spiritual services that has a murottal feature that can be used to reduce anxiety responses in patients. This application is used to help mothers with gestational age entering the period of seven months or third trimester who experience anxiety and irregular fetal heartbeat in primigravida mothers. The purpose of this study was to examine the effect of murottal therapy with the application of Spiritual Islamic Nursing Care (SINC) on the response of the third trimester of pregnancy. The research design used a quasi-experiment with a one-group pre and post-test design approach. The sample in this study amounted to 10 respondents using the accidental sampling technique. Data were collected using Doppler to measure the fetal heart rate (FHR), visual fetal movement, and the DASS (Depression Anxiety Stress Scale) questionnaire to measure the level of anxiety in pregnant women. Analysis of the data used was the Friedman test for fetal movement and fetal heart rate and the Wilcoxon test for the anxiety level of pregnant women. After the research, the results of statistical tests showed that there was a significant difference in the fetal heart rate and the anxiety level of the third trimester pregnant women before and after being given murottal therapy with the application of Spiritual Islamic Nursing Care (SINC). Therapy using murottal with the Spiritual Islamic Nursing Care (SINC) application provides recommendations that can be used in various health services for pregnant women.